Răspunsuri

Cel mai inteligent răspuns!
2014-04-03T17:53:43+03:00
 3x-1=-10                 -2x+4=x-5             \frac{x+2}{2} = \frac{x-1}{3}
 3x= -10+1               -2x-x= -5-4             Amplifici cu 3 prima fractie, iar a doua cu 2.             3x= -9 / :3               -3x= -9                 Si iti da:3x+6=2x-2                                                 x= -3                      x= 3                                 3x-2x= -2-6
                                                                       x= -8